Prevalence and antibiogram profile of Mycobacterium spp. in poultry and its environments - Reza, Md. Rubayet; Lijon, Md. Bakhtiar; Khatun, Mst. Minara; Islam, Md. Ariful (Journal of Advanced Veterinary and Animal Research, 2015)
In this study, an attempt was undertaken to know the prevalence and antibiogram profile of Mycobacterium spp. in poultry and its immediate environments. A total of 130 samples comprising of droppings (n=80), egg washing (n=18), drinking water (n=14), hand washing from farm workers (n=6) and litter (n=12) were collected from six poultry farms located in and around Bangladesh Agricultural University (BAU). Samples were inoculated onto 7H10 Middlebrook agar and incubated aerobically at 37ºC for 7-14 days. Identification of Mycobacterium spp. was performed by colonial morphology, acid fast staining, and biochemical tests. Molecular identification of Mycobacterium spp. at genus level was performed by polymerase chain reaction (PCR) assay targeting 65- kDa heat shock protein gene. Antibiogram profile of Mycobacterium spp. was performed against five antibiotics namely Rifampin, Azithromycin, Ciprofloxacin, Streptomycin and Doxycycline by disc diffusion method. Three Mycobacterium spp. were isolated from dropping samples of poultry. The overall prevalence of Mycobacterium spp. was 2.3% (n=3/130). All the isolates were resistant to Rifampin and sensitive to Azithromycin and Ciprofloxacin. Data of this study indicated that multidrug resistant Mycobacterium spp. are prevalent in the poultry farms of the study area which underscore the need of implementation of good biosecurity to poultry husbandry practice to ensure poultry and human health. http://dx.doi.org/10.5455/javar.2015.b118